(untitled) (Research, Society and Development, 2022)
Work is fundamental to human beings, and it is through work that man inserts himself into society. The objective was to highlight the factors that generate pleasure and suffering in nursing work. This study is an integrative review carried out in the databases of the Latin American Health Sciences Literature, the International Literature on Health Sciences, and the Bibliographic Database in the Area of Nursing in ​​Brazil, using as descriptors: pleasure, suffering, nursing and work. The sample consisted of 15 articles, without a temporal cut. Most of the investigations occurred in 2011, and they address the nursing area in the hospital context. Pleasure factors that stand out are those related to the recognition given by patients and their families, and the direct assistance to the patient, and those of suffering emerge mainly due to the death of a patient. It is concluded that such feelings are influenced by the relationships in the work environment, and that by evidencing the factors of pleasure and suffering in nursing work it is possible to stimulate people to build a more collaborative, constructive and fulfilling workplace for themselves.